2016
DOI: 10.1007/s00299-016-1958-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis

Abstract: Antagonists and sonication treatment relieved the structural barriers of Agrobacterium entering into cells; hindered signal perception and transmission; alleviated defense responses and increased cell susceptibility to Agrobacterium infection. Soybean gene expression analysis was performed to elucidate the general response of soybean plant to Agrobacterium at an early stage of infection. Agrobacterium infection stimulated the PAMPs-triggered immunity (BRI1, BAK1, BZR1, FLS2 and EFR) and effector-triggered immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Ideally, Rps11 genomic DNA would be transformed into soybean with its own promoter to best reveal the resistance conferred by Rps11 . However, given the large size of Rps11 from the TSR to the TTS (27.7 kb), the unclear boundary of its promoter region upstream of the TSR, as well as anticipated difficulty in transforming such a large segment in soybean—one of the most difficult crops to transform even for DNA fragments as small as a few kb 12 —we decided to use the promoter of an Arabidopsis ubiquitin gene, AtUbi3 (p AtUbi3 ), to drive Rps11 CDS (CDS- Rps11 ) expression (see “Methods”). The p AtUbi 3::CDS- Rps11 construct was introduced into an elite soybean variety 93Y21, which is susceptible to P. sojae races 25, 31, and OH12108-06-03.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, Rps11 genomic DNA would be transformed into soybean with its own promoter to best reveal the resistance conferred by Rps11 . However, given the large size of Rps11 from the TSR to the TTS (27.7 kb), the unclear boundary of its promoter region upstream of the TSR, as well as anticipated difficulty in transforming such a large segment in soybean—one of the most difficult crops to transform even for DNA fragments as small as a few kb 12 —we decided to use the promoter of an Arabidopsis ubiquitin gene, AtUbi3 (p AtUbi3 ), to drive Rps11 CDS (CDS- Rps11 ) expression (see “Methods”). The p AtUbi 3::CDS- Rps11 construct was introduced into an elite soybean variety 93Y21, which is susceptible to P. sojae races 25, 31, and OH12108-06-03.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, 16 DEGs referred to other crops to verify their homogous genes' expression between the SQ-1-treated and control plants were used. These genes included DFR2A (Sachiko et al 2013), ABCB1 (Cecchetti et al 2015), NEF1 (Ariizumi et al 2004), Ms1 (Yang et al 2007 which are involved in 'anther' development along with other genes such as GH3 (Feng et al 2015), FD (Kaur et al 2021), MKK4/5P (Zhang et al 2016). Gene expression was measured by qRT-PCR using gene-specific primers.…”
Section: Resultsmentioning
confidence: 99%
“…In soybean, genes involved in this metabolic process are also upregulated. But these genes' expression was reduced when a-aminooxyacetic acid (AOA, transformation promotion factor) was added in tissue culture following transformation [22]. This suggested that the upregulation of phenylpropanoid biosynthesis pathway may negatively affect the Agrobacterium infection.…”
Section: Discussionmentioning
confidence: 99%